IDIOMATIC EXPRESSION TRANSLATION STRATEGIES IN NOVEL “THE FAULT IN OUR STARS” - Sarah Melinda Angel; Evert H. Hilman; Evi Jovita Putri (IKIP Siliwangi, 2022)
This research aims to identify and analyze idiomatic expression translation strategy in the novel “The Fault In Our Stars” and to find out the most dominant strategy used in the translation. The method used in this research is a qualitative approach. This research uses semantic and syntactic strategy by using Chasterman' s theory, idiomatic translation strategy from Baker' s theories, and Searle's theory related to the speech act. The data presented in this research is based on John Green's novel, The Fault In Our Stars, there are 100 data was found. The result of this research asserts that Trope Change is the most common strategy, which is followed by Distribution as a Semantic Strategy. Meanwhile Scheme Change is the most common strategy, which is followed by Transposition as Syntactic Strategy. Strategy Idioms by